A Consequential Approach to Incorporating Spiritual Intelligence in the Workplace. - Moleka, Pitshou, Basikabio (My University, 2021)
Understanding the connection between spirituality and the workplace can be done in two ways. In this piece, I examine some of the benefits of adding spiritual intelligence into the workplace, including job satisfaction, organizational commitment, and corporate citizenship behaviors. The more organizations that embrace spirituality, both collectively and individually, the more benefits they will enjoy.
Keywords: Spiritual Intelligence; workplace spirituality; organizational commitment; job satisfaction; spiritual based organizations; organizational citizenship behaviors; corporate social responsibility; spiritual business model